Project control using S Curve in provision of pedestal crane at PT. Medco E&P Natuna - West Belut Platform - Rahmat, Rahmat; Putra, Dean Anggara; Restu, Rifo Nurlaksana; Imron, Jefri; Natawibawa, Marhaendra; Sumardiyanto, Hery; Munawar, Khairil; Junaedi, Thomas (Privietlab, 2025)
In the implementation of a project, three main aspects are indicators of the success of the project: cost, schedule, and quality. If the cost and time of project implementation are in accordance with the planning and quality requirements, then the project can be said to be successful. Time plays a significant role in construction management projects, where time is also a management function. With good and proper time control, obstacles to delays in project implementation can be avoided as much as possible. The purpose of this study was to determine the cause of the achievement or deviation of work between the realization in the field and the planned time schedule for the procurement of a pedestal crane unit for a new platform in the operational area of ​​ block-B-Natuna.